The Trigger for Improving the Performance of Construction Management Consultants PT Hariara Bona Perkasa (PT. HBP) - Stefan Gokparulian; Wita Juwita Ermawati; Furqon Syarief Hidayatulloh (PT Mattawang Mediatama Solution, 2024)
Construction Management Supervisory Consultant is a business entity or individual that has a function as a supervisor in a development project. The criteria for good or poor performance results are based on the suitability of the quality plan, budget, time and fulfillment of other company performance based on the contract that has been received, as well as the Conditional Work Plan (RKS) and the Framework of Reference (KAK). This study aims to explore the main triggering factors that cause the improvement of PT. HBP in supervisory work. This study uses a quantitative method, using the results of the t-test which is processed using the structural equation model (SEM) and the SPSS program. The results showed that there was a significant and positive influence between leadership, schedule management and risk management which was included in resources & capabilities and Project Management Competencies. The results of the research analysis show that the main factor that triggers the improvement of the company's performance of PT. HBP is risk management with a one-sample T-statistic value of 2,215 followed by leadership 1,890 and Schedule Management 1,179. Therefore, in this study, it can be concluded that risk management, leadership and schedule management are the main factors that trigger the improvement of PT. HBP.